THE CLASSIFICATION OF THE ANALYTICAL ESSAY AND ITS PRIMARY ATTRIBUTES - Rustamov Ilkhom Tursunovich (Web of Journals Publishing, 2024)
Analytical essays represent a ubiquitous academic task, necessitating students to engage in a critical examination of a subject, issue, or textual material, and present substantiated arguments and analyses. This article delves into the categorization of analytical essays and their fundamental characteristics, to furnish a thorough comprehension of this genre of scholarly writing.
Keywords: literature, textual materials, analytical essays, specific subject, essay genre, linguistic, distinctive features, pragmatic dimensions.